Optimization of the auxiliary ventilation system, based on experiments executed on a ventilation test bench for mines (2018)
In this study, the simulation results of the parameters concerning mine ventilation on a test bench are presented. Said investigation incorporated the previous design and implementation of a monitoring system at the laboratory. This was in order to calculate the fan efficiency, based on electrical measurements, and fluid mechanics (Bernoulli theory), and whose results can be observed in real time on a computer or through other similar means. The designed system monitors parameters present in the atmosphere of the test bench’s duct, such as temperature, air pressure, methane gas concentration, and electrical variables like voltage and current. The aforementioned observation is done through a graphical interface designed with LabView 2011 software. Tests were performed varying the accessories. The reduction percentage, allows one to infer that the duct section was adequately designed.